Estudo da corrosão do aço Maraging grau 300 em meio de cloreto contendo CO2 e CO2 / H2S - Avelino Júnior, Archimedes Fortes (2017)
Pipelines play an extremely important role in the world as a means of transporting gases and liquids over long distances from their sources to final consumers . However, numerous submarines structures are welded, and have dissimilar joints in conne ction with the flanges present s in submarine equipment s , these are subject to cathodic protection, occurring the release of hydrogen that migrates into the metal, favouring the p ropagation of defects . Pipelines play an extremely important role through the world as a means of tran sporting gases and liquids over long distances from their sources to ultimate consumers . Thus , corrosion in oil fields manifests itself in several media including corrosion by carbon dioxide (CO 2 ) and corrosion by hydrogen sulphide ( H 2 S). One possibility in the use of maraging steels would be the replacement of materials with little mechanical resistance (e.g., mild steel), in submarines applications that also require a good resistance to corrosion . Thus, t he corrosion behavior of the 18 % Ni 300 - grade maraging steel in a 0.6 mol L - 1 NaCl solution just saturated with CO 2 gas and in another medium containing H 2 S 1 mmol L - 1 and saturated with CO 2 , w as investigated by open circuit potential monitoring, linear potentiodynamic polarization a nd electrochemical impedance techniques along with products corrosion characterization techniques . Prior the corrosion tests, the maraging steel was solution - treated at 840 °C for 1 h and aged at 480 °C and 650 °C for 3 hours . The corrosion electrochemical tests proved that the precipitates formed during the aging thermal treatment was detrimental to corrosion resistance of the 18Ni 300 - grade maraging steel and the solution - treated condition presented the higher corrosion resistance than the aged samples an d the 1020 mild steel . X - Ray Photoelectron Spectroscopy and Scanning Electron Microscopy eletronic technique s allowed to identify FeCO 3 , Fe 2 O 3 , or Fe 3 O 4 , Ni(OH) 2 , NiO, TiO 2 and M oO 3 as the corrosion products in all 18 %Ni 300 grade maraging samples in 0.6 mol L - 1 NaCl medium, saturated with CO 2 gas . While in a 0.6 mol L - 1 NaCl solution medium containing H 2 S 1 mmol L - 1 and saturated with CO 2 , were allowed to detect FeCO 3 , Fe 2 O 3 , Fe (SO 4 ) and Fe(SO 4 ) 3 , NiO , Ni(OH) 2 , NiS, NiSO 4 , MoO 2 , Mo 2 O 3 and MoS 2 in corrosion products.